Effect of different non-chemical treatment methods on organic seed - Ertsey, A.; Berényi Üveges, K.; Radics, L. (International Journal of Horticultural Science, 2003)
The importance of ecological farming in Hungary is increasing. The utilisation of organic seed is regulated by national law. In our experiment the effect of two plant conditioning substantial: Biokál and Biomit Plussz were tested on the germination of seed. Our test plant species was garden pea (Pisum sativum L.), the most important vegetable in Hungary. The experiment was carried out in the germination laboratories of the National Institute for Agricultural Quality Control after international rules. The germination, the length of root and shoot were measured. 4 hours soaking of pea seeds in 30% solution of Biokál gave the best result. Our results could help to make the field emergence of organic seed faster and safer.